Bilateral congenital renal arteriovenous malformation: A rare entity with uncommon presentation - H, Radhiana; A, Mohd Shafie; MA, Mohd Ariff (IIUM Medical Journal Malaysia, 2009)
Renal arteriovenous malformation (AVM) is a rare congenital anomaly of the urinary system. We present a patient with bilateral renal AVMs who presented with back pain and microscopic hematuria. This case highlights the importance of careful diagnostic work-up in the evaluation of upper tract hematuria.